Cultures of Anti-Racism in Latin America and the Caribbean - Wade, Peter; Scorer, James; Aguil, Ignacio (University of London Press, 2019)
Latin America's long history of showing how racism can co-exist with racial mixture and conviviality offers useful ammunition for strengthening anti-racist stances. This volume asks whether cultural production has a particular role to play within discourses and practices of anti-racism in Latin America and the Caribbean. The contributors analyse music, performance, education, language, film and art in diverse national contexts across the region. The book also places Latin American and Caribbean racial formations within a broader global context. It shows that the region provides valuable opportunities for thinking about anti-racism, not least when recent political events worldwide have shown that, far from a 'post-racial' age, we are living in an era of intensified racist expression and racial injustice.